Speak mandarin in 30 days - Ibrahim Ismail 1924- (Golden Books Centre, 2006)
"Speak mandarin in 30 days" is a user friendly handbook with a chinese characters and romanized mandarin designed especially for those aspiring to study Mandarin quickly